PENGARUH LOKASI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus Pada UMKM CV. PIQPIKO INDONESIA) - Hakim; Sri Yatun (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This study aims to determine the effect of location and price on consumer purchasing decisions at CV. Piqpiko Indonesia. So the objectives to be achieved in this study are: 1) To determine the effect of location on consumer purchasing decisions at CV. Piqpiko Indonesia. 2) To determine the effect of price on consumer purchasing decisions in CV. Piqpiko Indonesia. 3) To determine the simultaneous effect of location and price on consumer purchasing decisions at CV. Piqpiko Indonesia. The research method used is a quantitative method. Research location in CV. Piqpiko Indonesia. The sample selection method in this study is Probability Sampling. The number of samples used was 113 respondents. Data analysis techniques used validity test, reliability test, classical assumption test, multiple linear regression test, hypothesis testing, and coefficient of determination test. The results of this study indicate that: 1) location has a positive effect on consumer purchasing decisions at CV. Piqpiko Indonesia. 2) price has a positive effect on consumer purchasing decisions in CV. Piqpiko Indonesia. 3) location and price on consumer purchasing decisions in CV. Piqpiko Indonesia.